The usefulness of cardiac computed tomography in the diagnosis of perivalvular complications in patients with prosthetic valve endocarditis. (25th November 2020) - Zatorska, K; Hryniewiecki, T; Zakrzewski, D; Nieznanska, M; Kusmierczyk, M; Michalowska, I
Abstract: Background and purpose of the study: Echocardiography remains the gold standard for the diagnosis of prosthetic valve endocarditis (PVE). But in around 15% of cases, its results can be false negative due to the acoustic shadow of artificial valves. The aim of the study was compare cardiac computed tomography (CT) with other imaging modalities in the diagnosis of perivalvular complications in patients with PVE. Material and methods: The study included 35 consecutive patients with PVE. Thirty of them had an artificial aortic valve (17- mechanical valve, 13-biological valve), 7-mechanical mitral valve, and one patient was after biological pulmonary valve implantation. Three patients were after aortic and mitral valve replacement. Each patient underwent transthoracic (TTE) and transesophageal (TEE) echocardiography. ECG-gated CT examinations were performed with a dual source CT system. All patients were qualified for surgical treatment. The assessment included the presence of vegetation, perivalvular abscess/pseudoaneurysm, inflammatory infiltration and prosthesis dehiscence. Results: Intraoperative assessment revealed the presence of vegetations in 16 patients. The sensitivity of echocardiography (TTE+TEE) and CT examinations was 100% and 93% respectively. Twenty one abscesses/pseudoaneurysms were found intraoperatively. The sensitivity of echocardiography and CT examinations was 76% and 85%, respectively. The analysis of total TTE, TEE and CT findings showed that supplementing echocardiography with CT had increased the sensitivity of the method for detecting abscess/pseudoaneurysms to 95%. In a patient in whom no abscesse was found, inflammatory infiltration was diagnosed in echocardiography. Inflammatory infiltration was diagnosed intraoperatively in 13 patients. The sensitivity of echocardiography and CT was 69% in both examinations. The sensitivity of the combination TTE + TEE + CT was 92%. Perivalvular leakage was found intraoperatively in 17 patients. The sensitivity of echocardiography and CT for the diagnosis of this complication was 100% and 87%, respectively. Conclusions: CT is better than echocardiography in diagnosing abscesses/pseudoaneurysms and has the same sensitivity in detecting inflammatory infiltration. Adding CT to echocardiography improves the sensitivity of these complications detection. CT is not superior to echocardiography in the diagnosis of vegetations and perivalvular leakage, but it can be a useful tool when echocardiography findings are inconclusive. Funding Acknowledgement: Type of funding source: None